Pengaruh Motivasi Dan Disiplin Terhadap Kinerja Pegawai Pada Kantor Dinas Sosial Provinsi Banten - Lisa Agustina; Yulis Tiawati (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
Motivation and work discipline play an important role in improving employee performenace, so in this case to get employee performance in line with what expected, the organization has the task of providing encouragement to employees, so that employees work diligently so as to achieve organizational goals, especially the office of social service of Banten Province. Based on the background of the problems described above, the formulation of the problem in this research is: 1). Is there an effect of motivation on employee performance at the Office of the Social Service of Banten Province, 2). Is there an effect of discipline on employee performance at the Office of Social Service of Banten Province, and 3). Is there an influence of motivation and discipline together?. The type of research used in this study is quantitative research, namely research that analyzes data using causal statistical figures, namely by using statistical formulas to help analyze data and facts obtained in make an accurate estimate of the characteristics of the entire population so that it is possible to achieve a description of each variable and the influence between variables at the Provincial Office of Social Affairs. This means that the variables of motivation and work discipline jointly (simultaneously) have a positive and significant influence on employee performance. Based on the statistical test results it can be seen clearly that partially all independent variables have an effect on the dependent variable. The influence of the two independent variables is positive, meaning that the better the motivation and work discipline, the better the employee performance will be. These results are in accordance with the proposed hypothesis. With the conclusion that motivation and discipline affect employee performance.